Push-pull effects of basal ganglia network in Parkinson’s disease inferred by functional MRI - Yuxin Wang; Zhiqi Jiang; Chunguang Chu; Zhen Zhang; Jiang Wang; Dianyou Li; Naying He; Chris Fietkiewicz; Changsong Zhou; Marcus Kaiser; Xuze Bai; Chencheng Zhang; et al. (npj Parkinson's Disease)
Abstract Deep brain stimulation (DBS) can ameliorate motor symptoms in Parkinson’s disease (PD), but its mechanism remains unclear. This work constructs a multi-scale brain model using the fMRI data from 27 PD patients with subthalamic DBS and 30 healthy controls. The model fits microscopic coupling parameters in the cortico-basal ganglia-thalamic neural loop to match individual connectivity, finding the “push-pull” effect of basal ganglia network. Specifically, increased GABAergic projection into the thalamus from basal ganglia worsens rigidity, while reduced GABAergic projection within the cortex exacerbates bradykinesia, suggesting that the dopamine deficiency induces the chain coupling variations to “push” the network to an abnormal state. Conversely, DBS can alleviate rigidity by enhancing GABAergic projections within the basal ganglia, and improve bradykinesia by reducing cortical projections to basal ganglia, exhibiting that DBS “pulls” the network to a healthy state. This work combines the microscopic and macroscopic neural information for understanding PD and its treatment.